Influence of Heterologous and Homologous Vaccines, and Their Components, on the Host Immune Response and Protection Against Experimental Caprine Paratuberculosis - Arteche-Villasol, Noive; Gutiérrez-Expósito, Daniel; Elguezabal, Natalia; Sevilla, Iker A.; Vallejo, Raquel; Espinosa, José; Ferreras, María del Carmen; Benavides, Julio; Pérez, Valentín (Frontiers in Veterinary Science, 2022)
Vaccination against paratuberculosis, a chronic disease of ruminants caused by Mycobacterium avium subsp. paratuberculosis (Map), has been considered as the most effective control method. However, protection is incomplete and the mechanisms operating in the response of the animals to vaccination are not fully understood. Therefore, this study analyzed the immune response and the effects on protection against Map infection, elicited by paratuberculosis (Silirum®) and tuberculosis (heat-inactivated M. bovis -HIMB) vaccines and their components in a caprine experimental model. Fifty goat kids were divided into ten groups (n = 5) according to their vaccination (Silirum®, HIMB and non-vaccinated), immunization (inactivated bacteria or adjuvant) and/or infection. Oral challenge with Map was performed 45 days post-vaccination/immunization (dpv) and animals were euthanized at 190 dpv. Peripheral immune response and proportion of lymphocytes subpopulations were assessed monthly by ELISA and flow cytometry analysis respectively. Local immune response, proportion of tissue lymphocyte subpopulations, Map detection (PCR) and histological examination were conducted in gut-associated lymphoid tissues. All infected groups developed paratuberculosis granulomatous lesions despite vaccination or immunization. Silirum® and HIMB vaccinated groups showed a considerable lesion reduction consistent with a significant peripheral cellular and humoral immune response. Besides, lower number of granulomas were observed in groups immunized with inactivated bacteria and adjuvants in comparison to non-vaccinated and infected group. However, despite not being significant, this reduction was even higher in adjuvant immunized groups which developed milder granulomatous lesion with no detectable peripheral immune responses associated to immunization. No changes in the peripheral and local proportion of lymphocyte subsets or local immune response were detected neither in relation with vaccination/immunization nor infection. Despite paratuberculosis and tuberculosis vaccination showed a partial and cross-protection against Map infection respectively, only histological examination could assess the progression of infection in these animals. In addition, the pattern observed in the reduction of the lesions in adjuvant immunized groups suggest the possible involvement of a non-specific immune response that reduce the development of granulomatous lesions.